Urgensi Restorative Justice dalam Penghentian Penuntutan oleh Kejaksaan dalam Perkara Pidana - Ary Chandra Kristiyawan; Akhmad Munawar; Hidayatullah (CV Rewang Rencang, 2023)
The restorative justice approach offers a progressive solution within Indonesia's criminal justice system to address the shortcomings of the retributive approach, which focuses primarily on punishment. This principle emphasizes victim recovery, offender accountability, and community involvement, thereby fostering more inclusive and substantial justice. The prosecution has strategic authority to discontinue prosecutions based on restorative justice, as stipulated in Article 14 Criminal Procedure Code and the Attorney General’s Regulation No. 15 of 2020. This study aims to examine the urgency of restorative justice principles in resolving criminal cases and the prosecutorial authority in discontinuing prosecutions under this approach. The findings indicate that restorative justice holds significant potential to overcome the weaknesses of the retributive criminal justice system. This approach effectively reduces court caseloads, prison overcrowding, and offender stigmatization while delivering more substantive justice for victims. The prosecutorial authority to discontinue prosecutions through this approach has proven to be an essential instrument in creating a more efficient, inclusive, and socially harmonious justice system.